FEE AUDIT SEBAGAI PEMODERASI PENGARUH KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Puspita, Made Ayu Prilla Winda; Utama, I Made Karya (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This research aimed to determine empirically the effect of audit quality and audit fee for the integrity of the financial statements and audit fees in the audit quality moderating influence on the integrity of financial statements. The theory used in this research is the theory of the Agency (Agency Theory). The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. In this study nonprobability sampling using sampling with purposive sampling technique. The data collected was conducted using non-participant observation. Data analysis technique used is Moderated Regression Analysis (MRA). The results showed that the quality of the audit and the audit fee positive effect on the integrity of financial statements. While the audit fee variable are not able to moderate the effect of audit quality on the integrity of financial statements.
Keywords: the integrity of financial statements; audit quality; audit fee